Eight ways to support faculty with Entrustable Professional Activities - Woods, Rob; Bouwsema, Melissa; Cheung, Warren; Hall, Andrew; Chan, Teresa; Paterson, Quinten (Canadian Medical Education Journal, 2024)
Competency Based Medical Education (CBME) is pushing the medical profession to be more accountable in our standards of assessment. This has led us to focus our efforts at the top of Miller’s pyramid, where we aim to see what the trainee ‘does’ in the clinical environment. In Canadian Royal College specialty training, this has come in the form of workplace-based supervision of trainees performing Entrustable Professional Activities (EPAs). This is unfamiliar territory for many residents and faculty, and implementation of an additional assessment process into already busy clinical practice has been particularly challenging. Because EPA assessments serve as significant contributors in new programs of assessment, failure to collect high quality EPA assessments threaten the validity of this new system. Understanding the barriers to and enablers of EPA acquisition can inform faculty development initiatives to ensure success. Based on our previous work studying early experiences of EPA assessment acquisition in Emergency Medicine, we have identified eight key concepts to guide faculty development initiatives, namely: the rationale for CBME, the ‘behind the scenes’ of CBME, how to construct rich narrative comments, effective use of supervision scales, the tension of EPA assessments being both formative and summative, the importance of a shared responsibility between residents and faculty for EPA assessment completion, familiarity with the suite of EPAs, and tips and tricks for incorporating EPA assessment completion into busy clinical practice. These key concepts can be integrated into an overall faculty development strategy for building this now essential skill set.